Curriculum, Teaching and Learning, and Assessments for Introductory Programming Course - Erum Mehmood; Adnan Abid; Muhammad Shoaib Farooq; Naeem A. Nawaz (IEEE Access, 2020)
Learning to program involves acquisition of various skills including problem solving, fundamental design techniques as well as critical thinking. Generally, most of the novice programmers struggle to develop all these important skill. The research community has addressed the problem in many different ways while involving improvisations in curriculum, pedagogical methods, cognitive aspects, supporting tools, and in designing assessments. This research aims to analyze and synthesize the existing literature in the aforementioned areas. Research articles pertaining to the area of Introductory Programming Courses (IPC) have been found using appropriate search queries, while nearly 60 research articles, published in last ten years, have been carefully selected by employing a systematic filtering process. The scope of this work only covers the research conducted for IPC in higher education. Main findings of this study show that “solution proposal” and “evaluation research” have been reported as two main research types adopted by these studies. Moreover, pedagogy, language choice and students' performance analysis are the most frequently addressed aspects of IPC; whereas, curriculum contents, assessment design, and teaching/learning through tools have appeared as less addressed aspects of IPC. Furthermore, a taxonomy of IPC has been presented based on the studied literature. Lastly, general considerations and future research directions have been presented for the practitioners and researchers in this area.